2008
DOI: 10.1002/ch.347
|View full text |Cite
|
Sign up to set email alerts
|

Interactional phenomenology of maternal and paternal hypnosis styles

Abstract: The study introduces an interactional analysis of subjective data (PCI and DIH questionnaires) from hypnotist and subject along with the concept of hypnosis styles (maternal/ paternal scores), in a real-simulator design. It was expected that the subjective experiences of maternal and paternal hypnotists (and their subjects) are different: 1) maternal style is more emotional regarding both interactional and experience parameters, while paternal style is rather cognitive and sovereign; 2) subjects can experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
0
12
0
3
Order By: Relevance
“…In our earlier study (Varga, Bányai, Józsa, & Gősi-Greguss, 2008), however, we reported the relationship between hypnosis style and interactional experiences (DIH). In the cases of maternal style hypnoses, there was no correlation between subjects' DIH scores and hypnosis style, but the same correlations were high in the hypnotists.…”
Section: Discussionmentioning
confidence: 79%
“…In our earlier study (Varga, Bányai, Józsa, & Gősi-Greguss, 2008), however, we reported the relationship between hypnosis style and interactional experiences (DIH). In the cases of maternal style hypnoses, there was no correlation between subjects' DIH scores and hypnosis style, but the same correlations were high in the hypnotists.…”
Section: Discussionmentioning
confidence: 79%
“…[ [17][18][19] The level of oxytocin (OT) and cortisol in the hypnotic interaction: traditional relaxational hypnosis…”
Section: The Focus Of the Study Main Finding Referencementioning
confidence: 99%
“…The relational experiences within psychotherapy of appropriate atmospheres give a chance for the modification of the pattern of representation of important relationships [ 54 ]. The patient may get a corrective experience in hypnosis, in this extremely enhanced emotional mutual attunement, when the hypnotist perceives, understands, and appropriately responds even to his/her unexpressed feelings [ 16 , 17 ].…”
Section: Hypnosis: Modelling Of Relational Patternsmentioning
confidence: 99%
“…Perhaps for this reason, the maternal-paternal axis scores for the hypnotists did not correlate significantly with any of a wide variety of subjective indices collected from their hypnotic subjects. The distinction between maternal and paternal styles of hypnosis also appears to have little effect on subjects’ hypnotic susceptibility, as measured by standardized hypnosis scales (Varga, Bányai, Jǒzsa, & Gősi-Greguss, 2008). Other research, however, indicates that the responsiveness of moderately hypnotizable people, in particular, may be sensitive to the quality of rapport with the hypnotist (e.g., Lynn et al, 1991; Sheehan, 1980).…”
Section: Research On Interpersonal Aspects Of Hypnosismentioning
confidence: 99%